A Case of Autism with Ring Chromosome 14 - Tajeran, Massoumeh (Iran J Public Health, 2013)
BACKGROUND: Autism is a complex neuropsychiatric disorder that manifests in early childhood. Although the etiology is unknown yet but, new hypothesis focused on identifying the key genes related to autism may elucidate its etiology. The main objective of the present study was to verify the value of karyotyping in autistic children and identifying association between chromosome abnormalities and autism. METHODS: We examined the peripheral blood lymphocytes cell culture for cytogenetic alterations by GTG-banding technique. The investigation was carried out on 50 autistic patients referred by Pediatric neurologist to Cytogenetic Laboratory in Khorasan-e-razavi Province, Iran. RESULTS: Using GTG-banding technique, the chromosome analysis of patients identified an unbalanced male karyotype with a r (14) in all 50 metaphaseswere examined. CONCLUSION: Since structural abnormalities may have a critical role in the etiology of autism, according to the region where is affected and number of related genes, therefore an outcome with wide spectrum of clinical manifestations could be expected. Furthermore by considering of recent study, the results indicated that there is an association between chromosome 14 with brain development and neurological disorders, but, in conclusion, it could not be suggested that in order to postulate cytogenetic testing in idiopathic autism patients, specifically screening for chromosome 14 which might has diagnostic value.